Comparison of Fixative Properties of Honey with Ethanol in Oral Cytological Smears - Khan, Mahmood Nawaz; Potekar, Ratnakar M; Nerune, Savitri M; Reddy, Anil K (Annals of Pathology and Laboratory Medicine, 2018)
Background: Fixation is an important step in cytopathological diagnosis. Ethanol is traditionally a popular and widely used fixative for cytopathological diagnosis. But ethanol is expensive and subjected to pilferage thus decreasing its ability. Ethanol denatures proteins and glycogen by precipitation. Hence in a search of better, ecofriendly and cost effective fixative, honey can be as efficient as ethanol in cytological fixation. Properties of honey such as high osmolarity, low pH and the presence of components such as ascorbic acid, hydrogen peroxide and phenol inhibine, all contribute to its anti-oxidative and antibacterial effects. Methods:- A cross sectional comparative study was carried out after ethical approval on healthy patients fulfilling the inclusion criteria referred to the Department of Pathology in BLDEU’S Shri B.M. Patil Medical College, Hospital and Research centre, Vijayapur. After informed consent two buccal smears were obtained from each individual, one was fixed in Ethanol and other was fixed in Honey (20%) for a minimum of 15 min. After staining, smears were scored for cytomorphological characters. Results:- Out of the 200 cases studied, honey fixed smears showed cytomorphological features similar to ethanol among which nuclear staining, clarity and uniformity of staining showed significant p value (p <0.05) where as cytoplasmic staining, cell morphology showed no statistical difference. (p>0.05) Conclusion: The present study offers an innovative proposal of using natural eco-friendly sweeteners, as fixative in cytopathology. The results are promising and invoke extensive large multicentric collaborative work to reach a global consensus on this fixative.